2014
DOI: 10.1007/s00432-014-1826-9
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of BTG3 promotes cell proliferation, migration and invasion and predicts survival in gastric cancer

Abstract: Down-regulation of BTG3 is closely associated with proliferation, migration and invasion in GC. It may be a novel prognostic biomarker for GC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 23 publications
7
31
1
Order By: Relevance
“…4a; Additional file 1: Table S2). Among these, FBXL5 and BTG3 have been reported to regulate EMT and cancer metastasis [2426]. Data from the microarray analysis was confirmed by qPCR in HeLa cells (Fig.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…4a; Additional file 1: Table S2). Among these, FBXL5 and BTG3 have been reported to regulate EMT and cancer metastasis [2426]. Data from the microarray analysis was confirmed by qPCR in HeLa cells (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…BTG3 was also shown to suppress proliferation and invasion of gastric and esophageal cancer cells [26, 44]. We demonstrated for the first time that FBXL5 and BTG3 are down-regulated in CC tissues and their downregulation are associated with worse prognosis in CC patients.…”
Section: Discussionmentioning
confidence: 90%
“…BTG3 expression was found to positively associate with favorable prognosis of gastric and ovarian cancers [13, 16]. Lv et al [14] found that the hepatocellular cancer patients with lower BTG3 expression had shorter overall survival time than the ones with higher BTG3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has demonstrated that BTG3 functions as a tumor suppressor in cancer progression. BTG3 expression is downregulated in lung adenocarcinoma, oral squamous cell cancer, or prostate cancer [19][20][21][22]. It was reported that BTG3 was a suppressor in the ESC progression [4].…”
Section: Discussionmentioning
confidence: 98%